ANALYSIS OF TRANSLATION TECHNIQUES IN THE SELECTED UNDERGRADUATE THESIS ABSTRACTS OF INDONESIAN LITERATURE STUDENTS OF MULAWARMAN UNIVERSITY AND ITS IMPACT TO TRANSLATION QUALITY - Rizkianty, Lana Rasita Safa; Kuncara, Singgih Daru; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
Translation is a process of transferring meaning from source language to target language concerning the stylistics and norm of the target culture. This research only focused on translation techniques and quality of four abstracts undergraduate thesis of Indonesia Literature Students of Mulawarman University. The researcher used qualitative methods, translation studies and investigator triangulation. Molina and Albir’s theory was used to analyze translation techniques, while the researcher used Nababan’s theory for translation quality. To reduce any subjectivity when assessing translation quality, the researcher asked for help from two English Literature lecturers of Mulawarman University to become the raters of this research. Ten translation techniques were found in all abstracts: amplification, borrowing, calque, compensation, generalization, literal translation, modulation, particularization, reduction, and transposition. The most technique used by all of the students is literal translation. There are twenty-two accurate data, seventeen acceptable data, and thirty-nine readable data from all abstracts. However, three inaccurate data, one unacceptable datum and one not readable datum were found.Keywords: translation techniques, translation quality, undergraduate thesis abstract